A nested case-control study of the association between exposure to polybrominated diphenyl ethers and the risk of gestational diabetes mellitus. (October 2018) - Liu, Xin; Zhang, Lei; Li, Jingguang; Meng, Guimin; Chi, Min; Li, Tiantian; Zhao, Yunfeng; Wu, Yongning
Abstract: Background: Gestational diabetes mellitus (GDM) is rapidly increasing worldwide. Exposure to endocrine-disrupting chemicals such as polybrominated diphenyl ethers (PBDEs) is thought to be a contributor to GDM, independent of diet and physical activity. Objective: The prospective association between PBDEs body burden in early pregnancy and GDM risk was investigated. Methods: A nested case-control study of 439 pregnant women was conducted between 2013 and 2015 in Beijing, China. Seven predominant PBDE congeners were measured in first trimester maternal serum by gas chromatography-high resolution mass spectrometry. Pregnant women were screened for GDM at 24–28 weeks of gestation using the oral glucose tolerance test. GDM was defined based on the diagnostic criteria set by China Ministry of Health. Conditional logistic and linear regression were used to estimate the association between PBDEs exposure and GDM risk, and PBDEs exposure and glucose level, respectively. Results: A total of 77 (17.5%) women developed GDM in this study. Median concentrations of PBDEs were higher in women with GDM. Analyses parameterizing PBDE concentrations as continuous variables suggested significant associations between BDE-153, -154, -183 and GDM risk with an estimated odds ratio of 4.04 (95%CI: 1.92, 8.52), 1.88 (95%CI: 1.15, 3.09) and 1.91 (95%CI: 1.31, 2.08), respectively. In the quartile analyses, a significant increase in the odds ratio of GDM was associated with the highest levels of BDE-153 (OR = 3.42 95%CI: 1.49, 7.89) and BDE-183 (OR = 3.70, 95%CI: 1.58, 8.65), whereas, BDE-154 demonstrated an inverted U-shaped association with GDM. In addition, BDE-153 and -154 were significantly positively associated with fasting glucose, and both 1 h and 2 h glucose level ( p < 0.05). Conclusions: These results suggest that exposure to PBDEs disturbs maternal glucose homeostasis and increases the risk of GDM. These findings should be replicated in future studies with a larger population and wider range of exposure. Highlights: A nested case-control study was conducted to examine the association of PBDEs with GDM. Maternal serum PBDEs levels were determined by GC-HRMS with high sensitivity. Positive association was found between some PBDEs and GDM risk. BDE154 revealed an inverted U-shaped association with GDM.